2016
DOI: 10.1016/j.actaastro.2015.12.039
|View full text |Cite
|
Sign up to set email alerts
|

The interference aerodynamics caused by the wing elasticity during store separation

Abstract: Air-launch-to-orbit is the technology that has stores carried aloft and launched the store from the plane to the orbit. The separation between the aircraft and store is one of the most important and difficult phases in Air-launch-to-orbit technology. There exists strong aerodynamic interference between the aircraft and the store in store separation. When the aspect ratio of the aircraft is large, the elastic deformations of the wing must be considered. The main purpose of this article is to study the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…8,30 The in-house CFD solver GFSI is used to solve the Euler equations, which has been fully tested for fluid-structure simulations in our previous works. 42,43,46,47 The integral form of the Euler equations can be written as:where W=[ρ,ρu,ρv,ρw,e]T is the vector of conservative variables, p is the density, u, v, and w are the velocity components in x, y, and z directions, and e is the internal energy per unit mass. F(W,Vgrid) is the inviscid flux vector.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…8,30 The in-house CFD solver GFSI is used to solve the Euler equations, which has been fully tested for fluid-structure simulations in our previous works. 42,43,46,47 The integral form of the Euler equations can be written as:where W=[ρ,ρu,ρv,ρw,e]T is the vector of conservative variables, p is the density, u, v, and w are the velocity components in x, y, and z directions, and e is the internal energy per unit mass. F(W,Vgrid) is the inviscid flux vector.…”
Section: Methodsmentioning
confidence: 99%
“…The same method has been successfully applied in our previous research. 42,46,47 The interpolation function is expressed as:where Θ(B) represents the boundary point set, w(Δxi) is the displacements of the node i, and Δxib=xibxi. The speed of projection is determined by the exponent a, which should be in the range of 3–5.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al [13] used the loose coupling method to analyze the influence of elastic and rigid wings on the separation trajectory of external stores and found quite different trajectories for these two cases. Yang et al [14] simulated the release of external stores for elastic wings based on the modal superposition method. They revealed that the elastic deformation of wings at the initial stage of separation greatly affects the trajectory of external stores.…”
Section: Introductionmentioning
confidence: 99%